Role of Microbes in Plant Growth and Food Preservation - Aqarab Husnain Gondal; Qammar Farooq; Irfan Hussain; Muhammad Danish Toor (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: Microbes perform better functions for agricultural production by promoting various direct and indirect mechanisms in soil and plants. If agricultural development is to satisfy the needs of an increasing global population, a deeper understanding of soil microbiology is needed. Furthermore, microbial biota such as yeast, bacteria etc., plays a significant role in food preservation by various mechanisms. Review results: Despite their pathogenicity, microbes play a substantial role in dispensing an assortment of fermented drinks and foods in the food industry and home. Probiotics, fermented foods and alcoholic beverages are flattering extra popular due to their health benefits and flavour. Furthermore, they increase the yield and growth of plants by improving mineral availability to the plants and by another mechanism. Review implementation: This present review also discusses the various organisms used in the agricultural processing of beverages and food and the benefits of using the following microbes in the beverage and food industry.